Dynamic barriers modulate cohesin positioning and genome folding at fixed occupancy - Rahmaninejad, Hadi; Xiao, Yao; Tortora, Maxime M.C.; Fudenberg, Geoffrey

(untitled) (Genome Research, 2025)
In mammalian interphase cells, genomes are folded by cohesin loop extrusion limited by directional CTCF barriers. This process enriches cohesin at barriers, isolates neighboring topologically associating domains, and elevates contact frequency between convergent CTCF barriers across the genome. However, recent in vivo measurements present a puzzle: reported CTCF residence times on chromatin are in the range of a few minutes, whereas cohesin lifetimes are much longer. Can the observed features of genome folding result from relatively transient barriers? To address this question, we develop a dynamic barrier model, where CTCF sites switch between bound and unbound states. Using this model, we investigate how barrier dynamics would impact observables for a range of experimental genomic and imaging data sets, including ChIP-seq, Hi-C, and microscopy. We find the interplay of CTCF and cohesin binding timescales influence the strength of each of these features, leaving a signature of barrier dynamics even in the population-averaged snapshots offered by genomic data sets. First, in addition to barrier occupancy, barrier bound times are crucial for instructing features of genome folding. Second, the ratio of boundary to extruder lifetime greatly alters simulated ChIP-seq and simulated Hi-C. Third, large-scale changes in chromosome morphology observed experimentally after increasing extruder lifetime require dynamic barriers. By integrating multiple sources of experimental data, our biophysical model argues that CTCF barrier bound times effectively approach those of cohesin extruder lifetimes. Together, we demonstrate how models that are informed by biophysically measured protein dynamics broaden our understanding of genome folding.